Corporate crime : contemporary debates (Toronto, 1995)
"Corporate crime inflicts massive harm on employees, consumers, workplaces, economies, and the environment, but there are inadequate controls and few deterrent mechanisms, and sanctions are mild relative to the harm done. There is little agreement on remedies and praxis, reflecting an underlying diversity of opinion on the causes of corporate criminality. Corporate Crime is a collection of original papers by many of the world's leading experts on corporate crime, and covers its causes, extent, and control. It provides discussions of all the major areas of corporate criminal conduct, looking at the relationship between corporate structure and corporate crime. It opens up debate on appropriate control strategies to deter perpetrators and minimize harm. The discussions centre around strategies to control the social, economic, and political costs of various kinds of corporate crime - within the corporate organization and the fields of finance, occupational health and safety, and environmental degradation. "